2009
DOI: 10.1074/jbc.m808363200
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Biochemical Characterization of the Wild Type PCSK9-EGF(AB) Complex and Natural Familial Hypercholesterolemia Mutants

Abstract: PCSK9 regulates low density lipoprotein receptor (LDLR) levels and consequently is a target for the prevention of atherosclerosis and coronary heart disease. Here we studied the interaction, of LDLR EGF(A/AB) repeats with PCSK9. We show that PCSK9 binds the EGF(AB) repeats in a pH-dependent manner. Although the PCSK9 C-terminal domain is not involved in LDLR binding, PCSK9 autocleavage is required. Moreover, we report the x-ray structure of the PCSK9⌬C-EGF(AB) complex at neutral pH. Compared with the low pH PC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
125
1
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(137 citation statements)
references
References 38 publications
10
125
1
1
Order By: Relevance
“…4), in agreement with its reported enhanced LDLR-binding affinity at neutral pH (11,18,23). Concentrations of secreted PCSK9, up to 12 nM (HepG2 cells; ϳ3ϫ endogenous levels; Fig.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…4), in agreement with its reported enhanced LDLR-binding affinity at neutral pH (11,18,23). Concentrations of secreted PCSK9, up to 12 nM (HepG2 cells; ϳ3ϫ endogenous levels; Fig.…”
Section: Discussionsupporting
confidence: 74%
“…Inhibition of the PCSK9-induced LDLR Degradation by EGF-AB-An EGF-AB peptide containing the LDLR binding site to PCSK9 was reported to inhibit the effect of exogenously added PCSK9 on LDLR degradation in either HEK293 or HepG2 cells (18,23,24). Although the effect of WT EGF-AB on naïve HepG2 cells was not reported, the inhibitory effect of the gain-of-function EGF-AB H306Y is best seen with exogenous PCSK9, with little effect on naïve HepG2 cells (18).…”
Section: Blockade Of Endocytosis In Hepg2 Cells Does Not Affectmentioning
confidence: 99%
“…Various approaches include humanized monoclonal antibodies, antisense oligonucleotides, RNA interference, and small molecule inhibitors. Recent success in studies with antibodies directed against PCSK9 has further increased interest in this target (19,20). As progress toward therapeutic intervention of PCSK9-LDLR interactions advances, it is important to understand the molecular basis of the biological events involved.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the structure determination of the complex under different pH conditions has suggested that the His-306 of EGF-A forms an additional salt bridge with the Asp-374 of PCSK9 at acidic pH (McNutt et al 2009), which should stabilize the PCSK9-LDLR complex under acidic conditions. In fact, the mutation of His-306 to Tyr is known to be associated with FH (Day et al 1997), and crystallographic analysis has demonstrated that the hydroxyl group of Tyr forms a stable hydrogen bond with Asp-374 even at neutral pH (Bottomley et al 2009;McNutt et al 2009). …”
Section: Asp-70mentioning
confidence: 99%
“…The structure determination of the EGF-AB pair in complex with PCSK9 has shown that the calcium-binding site of EGF-A serves as the binding site for PCSK9 (Bottomley et al 2009;Kwon et al 2008;McNutt et al 2009) (Fig. 3b).…”
Section: Asp-70mentioning
confidence: 99%